2020
DOI: 10.1038/s41598-020-67211-2
|View full text |Cite|
|
Sign up to set email alerts
|

Far-UVC light (222 nm) efficiently and safely inactivates airborne human coronaviruses

Abstract: A direct approach to limit airborne viral transmissions is to inactivate them within a short time of their production. Germicidal ultraviolet light, typically at 254 nm, is effective in this context but, used directly, can be a health hazard to skin and eyes. By contrast, far-UVC light (207-222 nm) efficiently kills pathogens potentially without harm to exposed human tissues. We previously demonstrated that 222-nm far-UVC light efficiently kills airborne influenza virus and we extend those studies to explore f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
540
1
23

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 521 publications
(575 citation statements)
references
References 39 publications
(61 reference statements)
11
540
1
23
Order By: Relevance
“…The UV light susceptibility of SARS-CoV-2 was also demonstrated, confirming the virucidal effect of the UV light [40]. In both studies, the effect of the higher UV light intensity was shown to have more virucidal effect, as expected [39,40]. In line with these data, we have shown the beta coronavirus is susceptible to the UV radiation and that this effect is directly proportional to the UV-light intensity.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The UV light susceptibility of SARS-CoV-2 was also demonstrated, confirming the virucidal effect of the UV light [40]. In both studies, the effect of the higher UV light intensity was shown to have more virucidal effect, as expected [39,40]. In line with these data, we have shown the beta coronavirus is susceptible to the UV radiation and that this effect is directly proportional to the UV-light intensity.…”
Section: Discussionsupporting
confidence: 83%
“…It was reported that the virus survival decreases with an increase in the UV energy [38]. Recently, Buonnano et al have demonstrated that alpha and beta coronaviruses are susceptible to the low dose of the UV light exposure, where 90% of virus inactivation was achieved in 8 minutes [39]. The UV light susceptibility of SARS-CoV-2 was also demonstrated, confirming the virucidal effect of the UV light [40].…”
Section: Discussionmentioning
confidence: 83%
“…The spectral ranges for UVA, UVB and UVC are 315 nm–400 nm, 280 nm–315 nm and 100 nm–280 nm, respectively. UVC is the one with the strongest antimicrobial/antiviral properties ( 74 , 75 ). With the rising healthcare awareness, some industry has demonstrated the effectiveness of radiation disinfection, especially UV light disinfection system on surface contamination, such as floors and equipment after the manual chemical disinfection process is completed ( 76 ).…”
Section: Ppe For Neurosurgical Proceduresmentioning
confidence: 99%
“…A laboratory study has shown that coronavirus could effectively be inactivated by UVC light ( 74 , 75 , 78 ). Nevertheless, the UV light device is not a substitute for handwashing, mask-wearing and distancing.…”
Section: Ppe For Neurosurgical Proceduresmentioning
confidence: 99%
“…The computer simulation of these respiratory aerosols is relevant, given that essential workers very often share close spaces. It would be convenient to simulate far-UVC light [20] and electrostatic precipitators [21,22] to eliminate SARS-CoV-2 in virulent PM 2.5 to control the air quality in such spaces. This new realistic computer simulation could help to capture real-world situations and thus examine more effective measures to prevent and control infectious spreading among essential workers during the COVID-19 pandemic.…”
Section: Simulation Limitations Advantages and Challengesmentioning
confidence: 99%